2020
DOI: 10.1007/s10620-020-06191-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Amitriptyline on Epigastric Pain Syndrome in Functional Dyspepsia Patients

Abstract: Aim To observe the therapeutic effect of low-dose amitriptyline (AMT) on epigastric pain syndrome (EPS) in patients with functional dyspepsia. Methods Sixty patients with EPS were randomly divided into the following two groups for a four-week clinical trial: routine treatment with pantoprazole (RT group) and the AMT group. The RT group was treated with 40 mg of pantoprazole once daily. The AMT group received 25 mg of AMT once daily before bedtime. The Nepean Dyspepsia Index (NDI) checklist, Hamilton Rating Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The search strategy generated 11 425 citations, 83 of which we retrieved for further assessment as they appeared to be relevant (Figure S2). Of these, 67 articles were eligible for inclusion, 31‐97 which reported on 71 separate RCTs comprising 19 243 participants. Of these, 12 535 received a drug for FD and 6708 a placebo, allocated as described in Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search strategy generated 11 425 citations, 83 of which we retrieved for further assessment as they appeared to be relevant (Figure S2). Of these, 67 articles were eligible for inclusion, 31‐97 which reported on 71 separate RCTs comprising 19 243 participants. Of these, 12 535 received a drug for FD and 6708 a placebo, allocated as described in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed characteristics of individual RCTs, including the comparisons made, are provided in Table S4. Eleven RCTs compared H 2 RAs with placebo, 31‐41 six trials, reported in five articles, compared acotiamide with placebo, 42‐46 five RCTs, reported in four articles, compared itopride with placebo, 47‐49,94 six trials compared itopride with domperidone, 50‐55 four RCTs, reported in three articles, compared standard‐dose and low‐dose PPIs both with each other and with placebo, 56‐58 four trials compared high‐dose PPIs with placebo, 59‐62 three RCTs compared standard‐dose PPIs with placebo, 63‐65 three trials compared low‐dose PPIs with placebo, 66‐68 three RCTs compared TCAs with placebo, 69,70,96 three trials compared 5‐HT 1A ‐receptor agonists with placebo, 71‐73 three RCTs compared antipsychotic drugs with placebo, 74‐76 two trials, reported in one article, compared tegaserod with placebo, 77 two RCTs compared H 2 RAs and 5‐HT 1A ‐receptor agonists both with each other and with mosapride, 78,79 one trial compared SSRIs with placebo, 80 one RCT compared SNRIs with placebo, 81 one trial compared TCAs and SSRIs both with each other and with placebo, 82 one RCT compared mirtazapine with placebo, 83 one trial compared mosapride with placebo, 84 one trial compared high‐dose, standard‐dose and low‐dose PPIs with each other and with placebo, 85 one RCT compared standard‐dose and low‐dose PPIs, and H 2 RAs with each other and with placebo, 86 one trial compared standard‐dose PPIs with H 2 RAs, 87 one RCT compared TCAs with high‐dose PPIs, 97 one RCT compared high‐dose PPIs with mosapride, 88 one trial compared standard‐dose PPIs with mosapride, 89 one RCT compared low‐dose PPIs with itopride, 90 one trial compared H 2 RAs with mosapride, 91 one RCT compared itopride with mosapride, 92 one trial compared mosapride with domperidone 93 and...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several patient‐reported outcome (PRO) questionnaires have been established to evaluate the severity of FD, including Dyspepsia Symptom Severity Index (DSSI), Gastrointestinal Symptom Rating Scale (GSRS), and Short‐Form Nepean Dyspepsia Index (SF‐NDI) 7–10 . Furthermore, Hamilton Anxiety Scale (HAMA) and Hamilton Depression Scale (HAMD) are also commonly used for evaluating the psychological status of FD patients 11 . However, none of the existing questionnaires can be considered sufficient as the primary outcome measure for FD trials according to the Rome criteria 5 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Furthermore, Hamilton Anxiety Scale (HAMA) and Hamilton Depression Scale (HAMD) are also commonly used for evaluating the psychological status of FD patients. 11 However, none of the existing questionnaires can be considered sufficient as the primary outcome measure for FD trials according to the Rome criteria. 5 Functional dyspepsia symptom diary (FDSD) is a newly symptom-focused PRO measure raised by the Patient-Reported Outcome Consortium's Functional Dyspepsia Working Group.…”
Section: Introductionmentioning
confidence: 99%